Classification of European Union Countries in the Context of Tax Burden: Cluster Analysis - Slezák, Jiří (ACTA VŠFS)
The tax burden affects a number of areas, including the economic and financial behavior of both legal entities and individuals. The aim of the article is to classify EU countries into groups based on selected tax burden indicators. The sample consists of 27 states of the European Union and the indicators used include direct taxes, indirect taxes, social contributions, taxes on consumption, on labor, on capital and implicit tax rate. In addition, the aim of the article is achieved through correlation and cluster analysis. Through cluster analysis, a total of 4 clusters were created for the period 2009-2021. The countries that joined the EU at the latest belong to the group of countries characterized by a lower tax burden. In contrast, most of the states that joined the EU earlier belong to the group of countries with a higher tax burden. In general, it can be said that countries also cluster on the basis of geographical or political characteristics. Through the cluster analysis, it was proven that there are significant differences between the states in the tax area and harmonization is not taking place, and there is thus further scope for tax harmonization. The contribution of the article is in the current assessment of the tax burden in EU countries and their classification according to similar tax systems for their discussion.